KARAKTERISASI FISIKO-KIMIA SERAT SABUT KELAPA TERAKTIVASI SEBAGAI MATERIAL RINGAN - Anugrah, Zhulfadillah; Wahyuni, Nelly; Rudiyansyah, Rudiyansyah (Indonesian Journal of Pure and Applied Chemistry, 2026)
Coconut fiber is used as a catalyst carrier due to its low density, which allows it to float and maximize the catalyst's performance. Various activation treatments, including organosolv and bleaching, are required to prepare the carrier. Both treated fibers were physicochemically characterized. The physical analysis included tests for moisture content, ash content, density, morphology, and elemental composition using Scanning Electron Microscopy-Energy Dispersive X-ray (SEM-EDX), alongside functional group analysis via Fourier Transform-Infra Red (FT-IR). Meanwhile, the chemical analysis determined the contents of hemicellulose, cellulose, and lignin. The density was 0.968 g/cm³ for the untreated fiber, 0.821 g/cm³ for the organosolv-treated fiber, and 0.225 g/cm³ for the bleached fiber. These results indicate that organosolv and bleaching treatments successfully reduce fiber density relative to the untreated sample, as corroborated by other physicochemical findings. Chemical analysis of the untreated, organosolv-treated, and bleached samples revealed hemicellulose contents of 20.149%, 16.396%, and 15.898%; cellulose contents of 42.871%, 47.631%, and 50.769%; and lignin contents of 29.639%, 29.464%, and 7.179%, respectively. Compared with the organosolv treatment, bleaching is the activation method that induces the most significant changes in physicochemical properties.